2018
DOI: 10.1007/s11695-018-3377-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of Opioid Analgesics Before and After Gastric Bypass Surgery in Sweden: a Population-Based Study

Abstract: In this nationwide study, we have showed that there is an increase in consumption of opioid analgesics after gastric bypass surgery in Sweden. The increase in the number of individuals with high opioid consumption in the total population was mainly due to an increase in the group of patients with a low consumption prior to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Among these, preoperative assessment of the risk of persistent J o u r n a l P r e -p r o o f postoperative opioid use, avoidance of long-acting opioid formulations, limiting the number of tablets prescribed at discharge and avoidance of automatic prescription refills as well as better education of healthcare professionals and patients are mentioned. Previous studies have reported increased use of opioids after bariatric surgery (7,32) . Probably, the association between opioid use preoperatively and the increased risk of an adverse outcome after bariatric surgery, as observed in this study, at least partly may be a contributing factor.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 96%
“…Among these, preoperative assessment of the risk of persistent J o u r n a l P r e -p r o o f postoperative opioid use, avoidance of long-acting opioid formulations, limiting the number of tablets prescribed at discharge and avoidance of automatic prescription refills as well as better education of healthcare professionals and patients are mentioned. Previous studies have reported increased use of opioids after bariatric surgery (7,32) . Probably, the association between opioid use preoperatively and the increased risk of an adverse outcome after bariatric surgery, as observed in this study, at least partly may be a contributing factor.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 96%
“…This is surprisingly because the massive weight loss, especially in DS, should reduce the patients' musculoskeletal pain. In recent years, there has been a concern about opioid analgesic use among bariatric patients, with 2 studies, 1 from the United States [21] and 1 from Sweden [22], reporting an overall increased use of opioids after bariatric surgery. It is possible that the effect on weight-related pain is overshadowed by the surgical trauma (bariatric operation and subsequent additional procedures) in combination with high prevalence at baseline, 2 important factors predisposing for chronic opioid use [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Four large prospective studies have been published which examine the prevalence of bariatric surgery patients who continue or initiate opioid use following bariatric surgery. 2,8,9,11 Raebel and colleagues 8,11 published prevalence rates and predictors of continued opioid use up to three years following bariatric surgery and new onset opioid use within the first post-operative year. Data were generated by analyzing the electronic health records of nearly 12,000 patients who underwent bariatric surgery at one of several geographically diverse centers across the US.…”
Section: Prevalence Of Opioid Use Before and After Bariatric Surgerymentioning
confidence: 99%
“…Most recently, prescription opioid use following RYGB bariatric surgery was reported from the Scandinavian Obesity Surgery Register (SOReg) 9 . Prescribing records were examined from a national registry from 35,612 patients who underwent a primary gastric bypass surgery in Sweden between 2007 and 2013.…”
Section: Prevalence Of Opioid Use Before and After Bariatric Surgerymentioning
confidence: 99%
See 1 more Smart Citation